20 essential games to study - Bycer, Joshua (CRC Press, 2019)
"The purpose of this book is to look over the past 35 years of games to discuss titles whose design deserves to be studied by anyone with an interest in game design. While there are plenty of books that focus on the technical side of Game Development, there are few that study the nature of game design itself. Featuring a mix of console and PC offerings, I purposely left off some of the easy choices (Mario, Starcraft, Call of Duty, Overwatch) to focus on games that stood out thanks to their designs"- Resumé vydavatel
Keywords: videohry; herní design; autorství; video games; game design; authorship; elektronické knihy; případové studie; electronic books; case studies